2017
DOI: 10.1186/s12912-017-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a modified brief assertiveness training for nurses in the workplace: a single-group feasibility study

Abstract: BackgroundEffective communication has a great impact on nurses’ job satisfaction, team relationships, as well as patient care/safety. Previous studies have highlighted the various beneficial effects of enhancing communication through assertiveness training programs for nurses. However, most programs take a long time to implement; thus, briefer programs are urgently required for universal on-the-job-training in the workplace. The purpose of this feasibility study was to develop and evaluate a modified brief ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
1
20
0
4
Order By: Relevance
“…This study demonstrated that this modified brief assertiveness training (total 180 min) could lead to consistent improvement in assertiveness among nurses on a long‐term basis. This matches and further replicates our preliminary results (Nakamura et al., ). In particular, the pre–post effect size of the modified brief training achieved a “small effect,” whereas previous brief trainings had “no effect” on improving nurses’ assertiveness (Honjo & Komada, ; Suzuki et al., ; Yamamoto et al., ; Zielinski & Williams, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This study demonstrated that this modified brief assertiveness training (total 180 min) could lead to consistent improvement in assertiveness among nurses on a long‐term basis. This matches and further replicates our preliminary results (Nakamura et al., ). In particular, the pre–post effect size of the modified brief training achieved a “small effect,” whereas previous brief trainings had “no effect” on improving nurses’ assertiveness (Honjo & Komada, ; Suzuki et al., ; Yamamoto et al., ; Zielinski & Williams, ).…”
Section: Discussionsupporting
confidence: 94%
“…An overview of the training programme is shown in Table ; the full original programme text written in Japanese is presented as an online supplemental file (see Nakamura et al, , for more details about the programme development). The training was developed based on existing assertiveness training literature (Alberti & Emmons, ; Hiraki, ) and shortened by four of the authors (NY, YN, HT and YS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, it seems reasonable to rely on psychological research not only for strategy development but also for implementation, e.g. training programs to promote appropriate assertiveness at work ( Thacker and Yost, 2002 ; Wilson et al, 2003 ; Nakamura et al, 2017 ). Additionally, future work is needed to determine appropriate conflict resolution strategies for more robot types (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, researchers have focused on improving healthcare professionals’ assertive communication and teamwork skills with some encouraging results (Lyndon et al, ). However, novice nurses are often hesitant to speak up or advocate for patients, particularly in countries such as Japan where there are deep‐seated cultural barriers to assertive communication (Nakamura et al, ; Suzuki, Azuma, Maruyama, Saito, & Takayama, ). Although training programmes have been introduced to address these issues, there are limited empirical data about the impact of such programmes on novice nurses’ communication behaviours.…”
Section: Introductionmentioning
confidence: 99%